Friction Tir Welding Using Round Welding Tool Probe on Aluminium Alloy AA6061 - LADIN, MUHAMMAD NASRULLAH BIN; Bin Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Friction Stir Welding (FSW) is a highly advantageous welding method compared to others, as it produces high-quality welds with minimal defects such as porosity and cracking. Additionally, FSW eliminates the emission of hazardous gases during the welding process. The selection of welding parameters is crucial for achieving a weld with strong mechanical properties at the joint. Consequently, this research project focuses on investigating the mechanical properties and microstructure of a 3 mm thick aluminum alloy AA6061 joint fabricated using FSW. The main objective of this project is to investigate the relationship between rotary speed and feed rate in friction stir welding by determining the mechanical properties and microstructure of the aluminum alloy AA6061 after the welding process and identifying the optimal parameters to produce the best and strongest joint. The projected methodology employs a series of process iterations with varying parameters. Specifically, different spindle speeds (1055 rpm, 1320 rpm, 1640 rpm, 1930 rpm, 2620 rpm) with a fixed feed rate of 14 mm/min. Tensile tests, microhardness tests, and microstructural analysis are conducted on the welded specimens to observe and collect the corresponding mechanical and microstructure properties. Subsequently, the obtained results are carefully evaluated. The experimental findings indicate that selecting suitable parameters leads to high mechanical strength, consistent microhardness, and fewer defects.